2022
DOI: 10.1088/1361-6579/ac5007
|View full text |Cite
|
Sign up to set email alerts
|

Current trends and opportunities in the methodology of electrodermal activity measurement

Abstract: Electrodermal activity (EDA) has been measured in the laboratory since the late 1800s. Although the influence of sudomotor nerve activity and the sympathetic nervous system on EDA is well established, the mechanisms underlying EDA signal generation are not completely understood. Owing to simplicity of instrumentation and modern electronics, these measurements have recently seen a transfer from the laboratory to wearable devices, sparking numerous novel applications while bringing along both challenges and new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 211 publications
0
17
0
Order By: Relevance
“…Whereas one study examining pregnant women [ 80 ] and one study examining working adults [ 81 ] found positive relationships between global subjective stress and current cortisol levels, other studies with working adults [ 82 ] and women with fibromyalgia [ 83 ] found no such association. Furthermore, one study among healthy adults suggests that several subjective responses to stress attenuate a positive effect of global subjective stress on momentary cortisol levels [ 42 ]. Positive relationships between cortisol and acute stressor severity during social interactions among school children [ 84 ] and women [ 76 ] were found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas one study examining pregnant women [ 80 ] and one study examining working adults [ 81 ] found positive relationships between global subjective stress and current cortisol levels, other studies with working adults [ 82 ] and women with fibromyalgia [ 83 ] found no such association. Furthermore, one study among healthy adults suggests that several subjective responses to stress attenuate a positive effect of global subjective stress on momentary cortisol levels [ 42 ]. Positive relationships between cortisol and acute stressor severity during social interactions among school children [ 84 ] and women [ 76 ] were found.…”
Section: Resultsmentioning
confidence: 99%
“…EDA reflects only the sympathetic nervous system activity of the ANS [ 40 ]. It has been used in the laboratory for a long time but due to advances in technology may be used in real world environments [ 34 , 41 ], making it an option for EMA studies [ 42 ]. Measurement is done e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Palm is chosen as the region of examination because it has wider (greater than 1 cm 2 as recommended by Tronstad et al 27 ) area of skin contact with the electrodes and density of SG is also relatively higher. 26,27 Specifically thenar and hypothenar region of palm offers higher skin conductance and response to electrical stimuli. 28 This system primarily consists of two Ag-AgCl electrodes placed on the palm at a 3 cm distance.…”
Section: Methodsmentioning
confidence: 99%
“…A simple system is designed to acquire an EDA signal by applying an electrical stimulus. Palm is chosen as the region of examination because it has wider (greater than 1 cm 2 as recommended by Tronstad et al 27 ) area of skin contact with the electrodes and density of SG is also relatively higher. 26,27 Specifically thenar and hypothenar region of palm offers higher skin conductance and response to electrical stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…• there is a substantial increase in the usability and accessibility of devices that measure EDA [3], [67], [69], [70]; • wearable technologies provide more opportunities to measure EDA in real-world settings [18], [41], [45]; • it is one of the most commonly used methods to measure physiological arousal [20], [46], [53].…”
mentioning
confidence: 99%